Lumpy Skin Disease (LSD): Etiology, Pathogenesis, Prevention and Control - Hendro Sukoco; Deka Uli Fahrodi; Nur Saidah Said; Marsudi Marsudi; Muhammad Irfan; Salmin Salmin; Sri Wahyuni; Khadijah Hardyanti (CV. Rayyan Dwi Bharata, 2023)
Lumpy skin disease (LSD) is one of the diseases that pose a threat to the livestock industry because it can cause large economic losses. The disease was first discovered in the country of Zambia in 1929. In Indonesia, LSD was first discovered in early 2022 in Indragiri Hulu Regency, Riau. This disease is caused by a virus belonging to the genus Capripoxvirus, subfamily chordopoxvirinae, family Poxviridae. The LSD virus has a limited host and does not infect non-ruminant hosts. A characteristic clinical symptom of LSD is the appearance of nodules on the skin. Diagnosis of this disease can be done by looking at typical clinical symptoms, laboratory tests such as virus isolation, serological tests (serum neutralization test, virus neutralization test (VNT), agar gel immune diffusion, indirect ELISA, and indirect fluorescent antibody technique (IFAT)), real time and conventional PCR, immunohistochemistry, LAMP, and IPMA. Prevention and control of LSD disease can be done in several ways such as vaccination, vector control, restriction of livestock traffic, strict quarantine and stamping out.